Interaction of silty sand and preformed corrosion products on N80 carbon steel in CO2 environment. (15th August 2022) - Chen, Longjun; Liu, Wei; Zhang, Tianyi; Dong, Baojun; Li, Hai; Sun, Yipu; Fan, Yueming; Zhao, Yonggang; Li, Wenqi
Abstract: The interaction of silty sand and corrosion products layer in sweet environment was evaluated. Corrosion protection was a function of two factors, i.e., adsorption and embedment of silty sand, and the presence of corrosion products layer. Silty sand could block ions transportation and slow down the dissolution of FeCO3 . The main protection was offered by corrosion products, this effect was more significant in the presence of a full coverage FeCO3 layer. FeCO3 -rich layer not only prevented the embedment of silty sand but also reduced the adsorption. Silty sand and corrosion products layer exhibited an obvious antagonism effect. Highlights: Corrosion reduction relied on silty sand and corrosion products. The main corrosion protection was offered by corrosion products. FeCO3 -rich layer prevented the embedding of silty sand and reduced the adsorption. Silty sand slowed down the dissolution of FeCO3 crystals. Silty sand and corrosion products layer exhibited an obvious antagonism effect.